ESRA19-0125 Pericapsular nerve group (PENG) block in the management of postoperative pain: case report of reprise total prostheses of ANCA. (30th August 2019) - Lentini, F; Marelli, J; Buccino, C; Barone, P; Zottola, V; Fusco, P
Abstract : Background and aims: Pericapsular nerve group (PENG) block can be considered a useful part of a multimodal analgesic treatment for post-operative pain after hip replacement surgery, even in extreme cases, such as replacement of antibiotic spacer. Methods: We report a case of a 69-year-old patient, carrier of the right hip antibiotic spacer, resulting in prosthetic infection. To this patient we performed PENG block with a mixture of Ropivacaine 0.5% and Dexamethasone 4 mg, for a total of 20 ml. After about 20 minutes the patient referred NRS=1. The operation was complicated by conspicuous blood loss and an important hypotension that required use of amines, colloids and blood and a semi-invasive monitoring by flow track system. In post-operative period, monitoring of vital parameters in intensive care was necessary. During this period, pain assessment was NRS = 0 and paracetamol was administered, 1 g twice a day. Results: The patient reported pain assessment of NRS = 0–3 for the whole hospital stay: during this period, she didn't need analgesic drugs. It has always been lucid and collaborative and vital parameters have always remained normal. Subsequently she was discharged to the structure for motor rehabilitation. Conclusions: PENG block was extremely effective for the control of intra and post-operative pain, allowing a rapid resumption of the patient's vital functions and preventing serious complications. This type of block is therefore effective for pain control in total hip replacement procedures, complicated by serious infections, in a multimodal management of post-operative pain control.